Evaluation of Guidance and Counseling Program during The Covid-19 Pandemic using The Kirkpatrick Model - Ari Novita Sari; Dina Widianti Anugraheni (Pamomong: Journal of Islamic Educational Counseling, 2022)
This evaluative research was conducted at a private elementary school in Bogor City to evaluate the Guidance and Counseling program during the Covid-19 pandemic using the Kirkpatrick model. Kirkpatrick's four-level evaluation was carried out using questionnaires, interviews, and field notes on students, Guidance and Counseling teachers, classroom teachers, and parents. The results of the reaction evaluation showed that most (56%) students were satisfied with the implementation of the guidance and counseling program. The program changed students' cognitive, affective and psychomotor aspects, with the highest percentage in the affective aspect (49%). Besides that, students also experienced a pretty good change in behavior after participating in the program. In addition, the classroom teachers, Guidance and Counseling teachers, parents, and students stated that the program during the pandemic positively impacted changing student behavior